Effects of Autonomous Driving Behavior on Intersection Performance and Safety in the Presence of White Phase for Mixed-Autonomy Traffic Stream. Issue 8 (August 2022) - Niroumand, Ramin; Hajibabai, Leila; Hajbabaie, Ali; Tajalli, Mehrdad
This paper studies the effects of different autonomous driving behaviors on an isolated intersection's safety and mobility performance measures in a mixed-autonomy environment. The movement of vehicles through the intersection is controlled by green, red, and "white" signal indications. Traffic operations during green and red signals are identical to a typical intersection. However, in the presence of the white phase, connected human-driven vehicles (CHVs) should follow connected and autonomous vehicles (CAVs) to pass the intersection safely. Three levels of driving aggressiveness for CAVs are considered: (1) cautious behavior, (2) normal behavior, and (3) aggressive behavior. The mobility and safety impacts of these CAV behaviors are studied based on different CAV market penetration rates and demand levels. The results indicate that a more aggressive CAV driving behavior leads to a lower average delay while increasing the average number of stops for CAVs. Additionally, a more aggressive CAV driving behavior leads to more frequent activation of the white phase that contributes to significant reduction in the speed variance. Moreover, the total number of rear-end near-collision observations with a time to collision of less than 10 s decreases as the CAV penetration rate and aggressiveness level increase. The main reason for this observation is that aggressive CAVs have higher acceleration and lower deceleration values and, therefore, have more flexibility to avoid a crash.